8 - A Relevant Education for African Development—Some Epistemological Considerations: 10.4314/ad.v29i1.22190 - Nyamnjoh, Francis A. (Africa Development, 2004)
This paper argues that education in Africa is the victim of a Western epistemological export that takes the form of science as ideology and hegemony. Under the Western epistemological export, education in Africa and/or for Africans has been like a pilgrimage to the Kilimanjaro of Western intellectual ideals, the tortuous route to Calvary for alternative ways of life. Sometimes, with rhetorical justification about the need to be competitive internationally, the practice has been for the elite to model education in Africa after educational institutions in the West, with little attempt at domestication. Education in Africa has been and mostly remains a journey fuelled by an exogenously induced and internalised sense of inadequacy in Africans, and endowed with the mission of devaluation or annihilation of African creativity, agency and value systems. Such cultural estrangement has served to reinforce in Africans self-devaluation and self-hatred and a profound sense of inferiority that in turn compels them to Tighten their darkness' both physically and metaphysically for Western gratification. The paper argues that the future of higher education in Africa can only be hopeful through a meticulous and creative process of cultural restitution and indigenisation even as African scholars continue to cooperate and converse with intellectual bedfellows in the West and elsewhere. If Africa is to be party to a global conversation of universities and scholars, it is only appropriate that it does so on its own terms, with the interests and concerns of ordinary Africans as the guiding principle.